THE PROTECTIVE ROLE OF NATURAL COUMARINS DERIVATIVES AND ANPRO SUPPLEMENT AGAINST AFLATOXIN B1 POLLUTION IN THE QUAILS COTURNIX JAPONICA DIET - Ban Ahmed; Bassam Ibrahim; Yasser Mustafa (Mesopotamia Journal of Agriculture)
This study aimed to investigate the potential of Coumarin C1 and C2 derivatives from apple seeds and Anpro supplementation to neutralize aflatoxin B1 in the quail diet., 3weeks -old quails were distributed into five-treatment each has 10 birds randomly. First treatment, negative control, in which the quails received not contaminated diet. Second treatment positive control the birds were fed on diet contaminated with AFB1 (0.5 mg/kg).  Third treatment the diet was contaminated with AFB1 (0.5 mg/kg). And treated with Anpro at 1 g/kg. Fourth treatment diets were contaminated with AFB1 and treated with C1 at 250 mg/kg, fifth treatment diets were contaminated with aflatoxin B1 and treated with C2 at 250 mg/kg. Result showed contamination diet with AFB1 caused reduction in PVC, RBC, Hb, blood glucose, total blood protein, and SOD and causes significant elevations in WBC and uric acid therefore biochemical variables can be boosted by adding Anpro, C1 and C2 to the diet contaminated with AFB1. For that, Anpro, C1, and C2 can serve as beneficial dietary supplements to the quail in order to counteract AFB1's detrimental effects.